Chemical characteristics and controlling factors of groundwater in an intensive surface water-groundwater conversion zone: a case study of the Zhengzhou section of the lower Yellow River - Xiangxiang, Cui; Lu, Liu; Yutong, Li; Xueqing, Zhang; Suhua, Meng; Shan, Lei (Frontiers in Environmental Science, 2025)
IntroductionThe Zhengzhou section of the lower Yellow River is an ecologically vulnerable region, where the groundwater chemistry has experienced significant variations due to the combined effects of natural factors and human activities.MethodsIn this study, we employed methods such as the Piper trilinear diagram, Gibbs plot, ion ratio coefficient method, and multivariate statistical techniques to explore the major controlling factors influencing groundwater chemical evolution.ResultsThe results indicate that 46% of shallow groundwater in the intensive conversion zone between surface water and groundwater is of the HCO3—Na·Ca·Mg water type. Influenced by lateral infiltration from the Yellow River, groundwater on both sides of the river evolves into Cl·SO4·HCO3 and Cl·HCO3 types. Groundwater near the riverbanks and ponds, directly replenished by Yellow River water or by leakage, is more significantly impacted by human activities compared to other regions. Factor analysis indicates that the chemical evolution of regional shallow groundwater is primarily controlled by factors such as mineral dissolution, human activities, and Yellow River water recharge. More pronounced water-rock interactions in unconfined aquifers, leads to an increase in the concentrations of conventional components like TDS and Mg2+.DiscussionDue to the long-term unidirectional transformation of surface water into groundwater, SO42- and Na+ in the groundwater are strongly influenced by surface water. NO3− is mainly affected by human activities, including domestic and agricultural activities. The concentrations of Fe and Mn are primarily influenced by the high background values of aquifer sediments and, to a lesser extent, by the significant enhancement of the aquifer’s reducing conditions, leading to higher concentrations of Fe and Mn in groundwater. The findings of this study provide theoretical and data-based support for the scientific formulation of groundwater protection and rational development measures.